Interactions of kratom alkaloids–mitragynine, 7-hydroxymitragynine, and mitragynine pseudoindoxyl with lipid bilayers: a molecular dynamics study - Mohd Zubri, Nur Syahirunelisa; Azhar, Nur Alya Amirah; Amran, Nur Aqasyah; Weng, Shirley In Siu; Awal, Asmah Awal; Jusoh, Siti Azma (Faculty of Pharmacy, 2025)
Kratom, a plant native to Southeast Asia, has gained attention as a potential alternative to opioids for pain relief and managing withdrawal symptoms. However, concerns about its safety persist due to reported adverse effects and drug interactions. Despite having at least 50 alkaloids, the pharmacological properties of kratom remain poorly understood due to limited research. In this study, molecular dynamics (MD) simulations were employed to investigate interactions of three major alkaloids of kratom—mitragynine, 7hydroxymitragynine, and mitragynine pseudoindoxyl—with a dipalmitoylphosphatidylcholine (DPPC) lipid bilayer. These alkaloids were initially placed in the aqueous phase in order to allow for unbiased diffusion into the lipid bilayer. The simulation revealed rapid permeation of all three compounds, with mitragynine exhibiting the fastest insertion time (~16 ns), followed by mitragynine pseudoindoxyl (~32 ns) and 7hydroxymitragynine (~33 ns). Upon entry, they predominantly localized near the lipid-water interface, forming hydrogen bonds with both water molecules and lipid phosphate groups. Mass density profiles and distance analyses further demonstrated that mitragynine and mitragynine pseudoindoxyl remained closer to the lipid headgroups, while 7-hydroxymitragynine penetrated deeper into the hydrophobic core. These findings highlight the amphiphilic nature of kratom alkaloids, with a tendency for hydrophobic interactions, consistent with their physicochemical properties. In conclusion, this is the first study that provides fundamental insights into the membrane partitioning behavior of kratom alkaloids, emphasizing their rapid permeation and bilayer localization. Such knowledge could guide the rational design of safer and more effective therapeutics for pain management, opioid withdrawal, and other pharmacological applications, addressing the need for alternatives to classical opioids.